PERAN KINERJA FINANSIAL DALAM MEDIASI HUBUNGAN ANTARA TINGKAT EMISI KARBON, PENGUNGKAPAN EMISI KARBON, DAN PERILAKU INVESTOR - Gita Ayu Tiara, (2022)
The aims of this study is to explore the role of financial performance in mediated relationship between carbon emission levels and carbon emissions disclosure on investor behavior in the form of abnormal returns. The sample of the study is a non-financial companies listed on the Indonesian Stock Exchange from 2018-2020. Samples were taken using purposive sampling method. This study finds that carbon emission level and carbon emission disclosure doesn't have any significant impact on investor behavior in form of stock's abnormal returns, this study also finds that financial performance (ROE) doesn't significantly affected by carbon emission level and carbon emission disclosure and its also don't have any significant effect on stocks's abnormal returns. Therefore this study finds that financial performance (ROE) doesn't have the ability to mediate the relationship between carbon emission level, carbon emission disclosure, and investor behavior. However this study has flaws and limitations, such as unstable economic conditiondue to covid-19 in Indonesia and limited data resources that lead to reduction of year sample. For further research this study suggest to use a control variable for the mediating variable which is return on equity.